INFORMATION COMPETENCIES OF THE TEACHERS - GREGANOVA, Radomira (Trends in education, 2013)
In this paper we focus on information pedagogical competence of teachers generally and than from the viewpoint of the students via questionnaire survey at the Faculty of Economics and Management SUA in Nitra.
Keywords: teachers; students; information pedagogical competence; questionnaire survey